The total sound power of some forced vibrations of a clamped annular plate in fluid - Rdzanek, W. P. (Archives of Acoustics, 2002)
The energetic aspect of sound radiation by a~clamped annular plate has been considered. The total sound power, active and reactive, was computed using the impedance approach, which makes possible to correctly design some acoustic systems. The plate was excited by the external pressure of an axisymmetric and time-harmonic distribution on the plate's surface. The Kelvin-Voigt theory of a~visco-elastic plate was employed. The results of a~modal analysis of an annular plate's in-vacuo motion were used.